2003
DOI: 10.1080/13557850310001631722
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of smoking behavior among Muslim Arab-American adolescents

Abstract: Social influences-based smoking prevention programs may be effective for adolescents from Muslim Arab cultures; however, they should be modified to address culturally based gender norms and may benefit from the incorporation of Islamic messages denouncing smoking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 51 publications
7
62
0
3
Order By: Relevance
“…In our review of published literature, we found studies on risk behaviors of middle and high school Muslim students in Western Europe (e.g., Amundsen, Rossow, & Skurtveit, 2005;Chédebois et al, 2009;Jayakody et al, 2011), but none on college students. The limited information that exists suggests that Muslim students report low prevalence of most behaviors (e.g., Amundsen et al, 2005;Chédebois et al, 2009;Jayakody et al, 2011), with female Muslim students reporting even lower prevalence than male Muslim students (e.g., Islam & Johnson, 2003). Furthermore, previous research did not explore whether Muslim engagement in risk behaviors were isolated incidents of risk, or a cluster of behaviors, as suggested by Jessor (1991).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In our review of published literature, we found studies on risk behaviors of middle and high school Muslim students in Western Europe (e.g., Amundsen, Rossow, & Skurtveit, 2005;Chédebois et al, 2009;Jayakody et al, 2011), but none on college students. The limited information that exists suggests that Muslim students report low prevalence of most behaviors (e.g., Amundsen et al, 2005;Chédebois et al, 2009;Jayakody et al, 2011), with female Muslim students reporting even lower prevalence than male Muslim students (e.g., Islam & Johnson, 2003). Furthermore, previous research did not explore whether Muslim engagement in risk behaviors were isolated incidents of risk, or a cluster of behaviors, as suggested by Jessor (1991).…”
mentioning
confidence: 86%
“…Furthermore, previous research did not explore whether Muslim engagement in risk behaviors were isolated incidents of risk, or a cluster of behaviors, as suggested by Jessor (1991). Only one study, to our knowledge, explored the protective influence of Islam on a risk behavior in Western nations (Islam & Johnson, 2003).…”
mentioning
confidence: 99%
“…Females in developing countries are reported to have a much lower prevalence of smoking (3.1%) compared to male smoking prevalence (32%) 17 . However, care should be taken when investigating epidemiological aspects of smoking in relation to gender due to denial behavior of some females, in conservative societies, who withhold information regarding their smoking in reaction to societal disapproval 18 . Furthermore, new trends of tobacco use are attracting the female populations, particularly in developing countries 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants (65.7%) grew up in homes with fathers who smoked cigarettes. Similarly, exclusive water-pipe smoking prevalence was high (44.2%) in this sample as well dual-smoking prevalence (e.g., smoking cigarettes and water-pipe) (55.8%) [42]. Similar to the reported prevalence of cigarette smoking, more male participants (66.6%) reported exclusive cigarette smoking than female participants (31.4%) while both groups reported experimenting with water-pipe smoking as young as 12 years of age In another study that examined smoking behaviors in 823 pregnant Arab American women who participated in the low-income nutritional supplemental program Women, Infants, and Children during the year 2002 in Michigan, 6% of the sample reported smoking while being pregnant [46].…”
Section: Data Synthesismentioning
confidence: 97%
“…Ancestry searches were used to identify any relevant studies that were not detected by the primary search. Because water-pipe smoking is a highly-prevalent behavior among Arabs and Arab Americans (practiced by an estimated 17% to 44.2% of this population) [10,41,42], studies that included water-pipe smoking or exclusively looked at water-pipe smoking behaviors among Arab Americans were also included. In addition, studies that included both adolescents and adults were included in this review.…”
Section: Search Strategymentioning
confidence: 99%